Cationic copolymerization of L, L‐lactide with hydroxyl substituted cyclic ethers1. (6th February 2015) - Basko, Malgorzata; Bednarek, Melania; Kubisa, Przemyslaw; Domb, Abraham; Slomkowski, Stanislaw
<x xml:space="preserve">Abstract</x> Cyclic ethers with 3‐, 4‐ and 5‐atoms in the ring containing hydroxymethyl substituents, acting as latent AB2 monomers, were copolymerized with L, L‐lactide by cationic mechanism with the aim of obtaining branched polylactide with multiple hydroxyl end‐groups. Hydroxymethyloxirane (glycidol) (three‐membered ring) was quite effective in introducing branching, resulting medium molecular weight polymers were characterized by GPC, NMR, MALDI‐TOF and thermal analysis methods. Hydroxymethyloxetane (three‐membered ring) also gave branched polymers although this comonomer was less effective in introducing branching than glycidol. Hydroxymethyloxolane (five‐membered ring) did not copolymerize, acting only as initiator of lactide polymerization; thus, resulting product was lactide homopolymer containing tetrahydrofuran moiety as head‐group. Copyright © 2015 John Wiley & Sons, Ltd.